Perilaku Sehat Usia Lanjut Di Panti Werdha Senja Cerah, Kotamadya Manado - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The purpose of this study was to know the association between the Psychosocial Potency with the healthy behavior of the elderly at institutionalized Senja Cerah, Kotamadya Manado. This study was conducted using quantitative and qualitative methods with a cross sectional study design. The number of sample were 86 elderly, consist of 63 female and 23 male. Data were collected using questionnaire and in depth interview and analyzed using bivariat. Statistical examination was carried out using Pearson's correlation. The result of this study shows a positive correlation between Psychosocial Potency with the healthy behavior of the elderly, in the meaning high psychosocial potency can be increased using the healthy behavior. r = 0.416 p < 0.05. Psychosocial potency in the form of social support not significantly correlated with the elderly healthy behavior. r = 0.017 p > 0.05 Key word: elderly psychosocial potency healthy behavior